Educational opportunities in Oklahoma for preparing colored home economics trained persons for professional and occupational advancement - Gandy, Lenouliah E., author; Morgan, David H., advisor; Williamson, Maude, committee member; Holman, Mary V., committee member; Elliff, Rowan, committee member; Betts, Gilbert L. (Gilbert Lee), 1893-1972, committee member (Colorado State University. Libraries, 1942)
To view the abstract, please see the full text of the document.
Keywords: Home economics -- Oklahoma; Education -- Oklahoma; African Americans -- Education; African Americans -- Oklahoma